Greek art and archaeology - Pedley, John Griffiths (Boston Prentice Hall, 2012)
Synopsis: Now in its fifth edition, Greek Art and Archaeology charts the achievements of Greek art and civilization over 3000 years, from the abstract figures of the Cycladic islands and the mighty palaces of Crete to the baroque sculptures and complex architecture of the Hellenistic kingdoms. This new edition introduces a wealth of new material including discussion and illustration of new findings at early Bronze Age sites in Crete and the Cycladic Islands, the fourteenth century BC Uluburun shipwreck, the evolution of coinage in the Greek city states, the purpose and function of temples and the Kouros figure in Archaic Greece, new ideas on interpreting the frieze of the Parthenon, and expanded coverage of the wealth and culture of Macedon. In addition, there are over 50 new color images of key works in the history of Greek art, including the Hera of Samos, the Motya charioteer, the Parthenon frieze, and newly commissioned photography of one of the masterpieces of later Greek art, the Alexander Sarcophagus. Written in a clear style, the book neatly balances lucid description with insightful interpretation and discussion. Intended for students and art enthusiasts of any age, it provides the most accessible and authoritative introduction to Greek art and archaeology available today.
Preface -- Introduction -- Recovery of antiquity -- Eighteenth century -- Nineteenth century -- Twentieth century Twenty-first century -- Literary sources -- Development of classical archaeology -- Culture and society: Harriet Boyd Hawes: American pioneer -- Map the Greek world -- Chapter 1: Aegean In The Third Millennium c3000-2000 BC -- Chronology -- Crete -- Architecture -- Pottery and stonework -- Cyclades -- Architecture -- Sculpture -- Pottery and stonework -- Greece -- Architecture -- Pottery -- Map Minoan Crete and the Bronze Age Aegean -- Chapter 2: Middle Bronze Age c2000-1550 BC 44 -- Crete -- Architecture -- Sculpture -- Pottery -- Cyclades -- Architecture -- Pottery -- Greece -- Architecture -- Pottery -- Troy -- Controversies and issues: Art And The Forgery -- Controversies and issues: Heinrich Schliemann: scholar or rascal? -- Controversies and issues: Priam's treasure: doubts and difficulties -- Chapter 3: Late Bronze Age c1550-1100 BC 60 -- Shipwreck off Uluburun -- Crete -- Architecture and wall painting -- Sculpture and pottery -- Scripts -- Minoan religion -- LM III period -- Cyclades -- Keos -- Melos: Phylakopi III -- Minoan Thalassocracy -- Pottery -- Thera -- Volcanic eruption -- Melos: Phylakopi IV -- Greece -- Grave circles at Mycenae -- Architecture and wall painting -- Sculpture and pottery -- Troy and the end of the Bronze Age in Greece -- Culture and society: Linear B And Its Decipherment -- Chapter 4: Dark Age And Geometric Greece c1100-700 BC -- Architecture -- Sculpture -- Pottery -- Colonization -- Culture and society: Burying The Dead -- Map the Greek world to c400 BC -- Map south Italy and Sicily -- Chapter 5: Orientalizing Period c700-600 BC -- Pottery -- Corinth -- Athens -- East Greece and the Islands -- Architecture and architectural sculpture -- Sculpture -- Culture and society: drinking and dining: the symposium -- Culture and society food -- Chapter 6: Archaic Greece c600-480 BC -- Athens -- Architecture and architectural sculpture -- Orders -- Doric temples -- Ionic temples -- Cyclades -- Temple functions -- Sanctuaries -- Doric and ionic treasuries -- Sicily and South Italy-- Athens -- Sculpture -- Kouroi -- Korai -- Reliefs -- Pottery -- Athens -- Corinth -- Laconia, East Greece, and the West -- Athenian red-figure -- Culture and society: Coins and coinage -- Controversies and issues: Getty Kouros: is it for real? -- Culture and society: Connoisseurship -- Map Greece and the Aegean -- Chapter 7: Period Of Transition c480-450 BC -- Athens and the Western Greeks -- Women's world -- Architecture and architectural sculpture -- Aegina -- Olympia -- Olympic games -- Sicily and South Italy -- Athens -- Sculpture -- Pottery and wall painting -- Culture and society: Silver mines and silver -- Coins at Athens -- Culture and society: Homosexuality -- Chapter 8: High Classical Period c450-400 BC -- Peloponnesian war -- Architecture and architectural sculpture -- Athens -- Sicily and South Italy -- Sculpture -- Pottery and wall painting -- Controversies and issues: Lord Elgin and the Parthenon Marbles -- Map Attica -- Chapter 9: Fourth Century c400-300 BC -- Architecture and architectural sculpture -- Bassae -- Epidauros -- Athens 297 -- Olynthos -- Priene -- Halikarnassos -- Sculpture -- Alexander the Great -- Pottery -- Wall painting and mosaics -- Macedon -- Vergina -- Pella -- Lefkadia -- Controversies and issues: Theater at Athens: were women in the audience? -- Controversies and issues: Vergina: the tomb of Philip (but which Philip?) -- Map the Greek world c400-30 BC -- Chapter 10: Hellenistic Period c323-31 BC -- Rome and Greece -- Architecture -- Pergamon -- Kos -- Magnesia and Didyma -- Athens -- Miletus -- Syracuse -- Sculpture -- Wall painting and mosaics -- Pottery -- Culture and society: Antikythera mechanism -- Culture and society: Salvage archaeology -- Conclusion -- Chronology -- Glossary -- Select bibliography -- Photographic credits -- Index.
Includes bibliographical references and index.
Keywords: Art, Greek; Greece -- Antiquities